Repurposing the inhibitors of COVID-19 key proteins through molecular docking approach. (November 2021) - Alghamdi, Huda Ahmed; Attique, Syed Awais; Yan, Wei; Arooj, Anam; Albulym, Obaid; Zhu, Daochen; Bilal, Muhammad; Nawaz, Muhammad Zohaib
Graphical abstract: Highlights: Inhibitors of the viral proteases and structural proteins are evaluated. Identification of putative inhibitors of key proteins involved in viral replication, and survival. Exploration of pharmaceutical properties of these inhibitors for predicting drug suitability against COVID-19. Trandolapril, Benazepril, and Moexipril were the best non-carcinogenic and non-toxic potential inhibitors. Abstract: The severe acute respiratory syndrome coronavirus 2, famous as COVID-19, has recently emerged as a novel virus and imposed an unrecoverable loss to global health and the economy. At present, no effective drug against COVID-19 is available and currently available viral drugs targeting the viral key proteins of related RNA viruses have been found ineffective against COVID-19. This study evaluated the inhibitors of the viral proteases and other structural proteins, including Mpro (Main protease), RdRp (RNA-dependent RNA polymerase), and spike glycoprotein from synthetic and herbal sources. The molecular docking-based approach was used to identify and evaluate the putative inhibitors of key proteins involved in viral replication and survival. Furthermore, the pharmaceutical properties of these inhibitors were explored to predict the drug suitability as a therapeutic agent against COVID-19 by considering adsorption, distribution, metabolism, and excretion (ADME) using Lipinski's rule or SwissADME. Trandolapril, Benazepril, and Moexipril were evaluated as the best non-carcinogenic and non-toxic potential inhibitors of spike glycoprotein, Mpro, and RdRp, respectively. The drugs showed significant binding affinities against the active sites of respective SARS_CoV-2 target proteins; hence, they can be used as potential therapeutic agents for the treatment of COVID-19.